THE INFLUENCES OF SOME VARIABLES ON ATTITUDES OF SPECIAL EDUCATION TEACHERS TOWARDS EDUCATING PUPILS WITH AUTISM IN REGULAR SETTINGS - Ahmed Elhassan, Hamid Hassan; Ahmed, EldoodYousifEldood; Alasmari, Abdul-alaziz (International Journal of Research -GRANTHAALAYAH, 2015)
All special needs teachers want their children to be accepted by their peers have friends and lead “regular” lives. Inclusive settings can make this vision a reality for many children with disabilities. So that we conducted this study to know the influences of some variables on attitudes of special education teachers towards educating students with autism in regular settings. The researchers used descriptive statistic methods. Questioner technique is used as method of data collection. Study group included 150 special education teachers from Abu Areech Learning administration, 70 teachers were selected randomly as sample. The data was analyzed by using SPSS program. The results are as following: There are no significant differences in attitudes of special education teachers towards inclusive settings according to interaction with disabled, there are no significant differences in attitudes of special education teachers towards inclusive settings according to the class size. There are significant differences in attitudes of special education teachers towards inclusive settings according to the training courses and there are significant in attitudes of special education teachers towards inclusive settings according to the qualification.